Nominal wage adjustment, demand shortage and economic policy - Yoshiyasu Ono; Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2009)
We formulate nominal wage adjustment by incorporating various concepts of fairness. By applying it into a continuous-time money-in-utility model we examine macroeconomic dynamics with and without a liquidity trap and obtain the condition for persistent unemployment, and that for temporary unemployment, to occur. These conditions turn out to be critical, since policy implications significantly differ between the two cases. A monetary expansion raises private consumption under temporary unemployment but does not under persistent unemployment. A fiscal expansion may or may not increase short-run private consumption but crowds out long-run consumption under temporary unemployment. Under persistent unemployment, however, it always increases private consumption.
Keywords: E52; E31; 330; Wage adjustment; Fairness; Phillips curve; Demand shortage; Persistent stagnation; Lohnniveau; Gerechtigkeit; Zeitpräferenz; Phillips-Kurve; Gesamtwirtschaftliche Nachfrage; Wirtschaftspolitik; Dynamische Optimierung; Theorie